Pengaruh Struktur Modal Terhadap Kinerja Perusahaan Pada Perusahaan Manufaktur - Salma Taqwa (Wahana Riset Akuntansi, 2016)
This paper mainly studies the influence of capital structure on firm’s performance. The investigation has been performed on samples of 23 companies listed on the stock exchange Indonesia during the period 2011-2014. Performance measurements used in this study, are: the Return on Asset (ROA) and Return on Equity (ROE) as the dependent variable and  Debt to Equity Ratio (DER) as an independent variable. The study also used ownership structure as a control variable. Using E-views to process data, it is obtained that firm’s performance is related to capital structure while the firm’s performance measured by ROE is not related to capital structure as measured by DER. On the other hand, there is no relation between control variable and firm’s performance measured by ROA and ROE. Keywords: firm’s performance, capital structure, ownership structure